BRAC Education Programme (BEP) NFPE phase III June 1999 May 2004: Mid term review 2001 - Biervliet, Wim E.; Bourgeois, Edwin; Jahan, Momtaz; Lutfunnessa, Shireen (© BRAC, 2016)
1. MTR TOR AND implementation 2. Key success indicators: the status and constraints in program implementation at mid-term 3. Monitoring and research 4. Enhancing quality: EDU and field structure 5. Capacity building and staff development 6. Enhancing and quality of learning and teaching 7. Continuing education and APON 8. Issues and recommendations.